V2O5 nanoribbons/N-deficient g-C3N4 heterostructure for enhanced visible-light photocatalytic performance. (26th March 2023) - Hassan, Ahmed E.; Elsayed, Mohamed Hammad; Hussien, Mai S.A.; Mohamed, Mohamed Gamal; Kuo, Shiao-Wei; Chou, Ho-Hsiu; Yahia, Ibrahim S.; Mohamed, Tarek A.; Wen, Zhenhai
Abstract: Visible-light-induced heterostructure photocatalysts have been regarded as promising candidates in clean energy production and environmental treatment of organic pollutants. In this study, we have prepared nanocomposites of V2 O5 /N-deficient g-C3 N4 (VO/Ndef-CN), which have been characterized by a variety of techniques. The as-synthesized nanocomposites show efficient bifunctional photocatalytic properties toward hydrogen generation and pollutants degradation (dye and antibiotic). The optimized 5VO/Ndef-CN photocatalyst exhibits improved photoactivity for H2 production (5892 μmol g −1  h −1 ), with a high quantum yield of 6.5%, and fast degradation of organic pollutants, as well as high photocatalytic stability under visible light irradiation. The high photocatalytic efficiency is due to the presence of N defects and S-scheme heterojunction formation, which leads to rapid charge separation, enhanced visible-light absorption, and increased active sites. Furthermore, the possible activity-enhanced mechanism and the photodegradation pathway are proposed based on the experimental and density functional theory (DFT) investigations. Graphical abstract: Image 1 Highlights: V2 O5 nanoribbons/N-deficient g-C3 N4 was synthesized as S-scheme heterojunction photocatalyst. The photocatalyst showed high visible-light photocatalytic activity for H2 production and pollutants degradation. The photocatalyst exhibited excellent stability. The photocatalytic mechanism was studied based on the experimental and DFT calculations.